Combined Effect of Polar Substituents on the Electronic Flows in the Carotenoid Molecular Wires. Issue 33 (2nd July 2013) - Zhao, Yanan; Lindsay, Stuart; Jeon, Sunhwa; Kim, Hyung‐Jun; Su, Liang; Lim, Boram; Koo, Sangho
<x xml:space="preserve">Abstract</x> Carrot wires: Carotenoid molecular wires containing a pair of polar aromatic substituents have been synthesized to probe the combined effect of electron‐withdrawing and ‐donating groups as conductance modulators (see figure). The total conductance values of the carotenoid wires are mostly controlled by electron‐withdrawing substituents, whereas fine tuning is possible by way of the electron‐donating substituent.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>